THU0134 Rheumatoid Vasculitis: A Decline in the XXI Century. (9th June 2015) - Riveros Frutos, A.; Martínez-Morillo, M.; Rodríguez Muguruza, S.; Sanint, J.; Prior, A.; Holgado, S.; Mateo, L.; Cañellas, J.; Tena, X.; Olivé, A.
Abstract : Background: Rheumatoid vasculitis is an extra articular manifestation of rheumatoid arthritis (RA), that occurs during the course of long standing disease. It is associated with a poor prognosis Objectives: To describe the clinical characteristics, incidence, treatment, and outcome of patients diagnosed with rheumatoid vasculitis (RV) at a Rheumatology service of a University hospital during the last 30 years Methods: Retrospective study (1984-2014). Location: University hospital. Referral area: 850.000 inhabitants. Medical records of patients with diagnosis of RA were reviewed, from the Rheumatology service data base. Inclusion criteria: patients with RV with histopathological confirmation of vasculitis or high suspicion based on clinical or radiological (arteriography) findings (according to Scott and Bacon criteria) Results: A total of 18 patients were included: 6 (33.3%) females and 12 (66.7%) males, mean age of 10.13±66.5 (49-83 years). The clinical characteristics of patients are listed in Table 1 . The most common clinical presentation was skin involvement with palpable purpura and digital ulcers. Other common manifestations were multineuritis and systemic involvement. Heart, eyes, or pulmonary involvements secondary to RV were absent. Laboratory tests at diagnosis of RV, showed an increased of acute phase reactants and anemia. All patients had a positive rheumatoid factor, citrullinated antibodies were determined only in five (27.8%) cases, being positive in all of them.Histological confirmation was possible in 8 (44.4%) cases, in the other 10 (55.6%) cases the diagnosis was made with clinical or radiological findings. Most patients were treated with pulse steroids associated with other immunosuppressive drugs. Seven (38.9%) patients died. Three of them (16.7%) secondary to vasculitis, and 4 (22.2%) of other causes.The incidence of rheumatoid vasculitis has decreased considerably in the last decade. Just 4 cases were diagnosed during the last 10 years. Conclusions: RV is a rare complication of RA. Cutaneous and neurological involvement is more common. It is more frequent in male smokers with seropositive and nodular RA. Histological diagnosis is difficult. Currently the incidence is decreasing, however mortality is still high. Disclosure of Interest: None declared